Electrochemical Sensors Based on Carbon Nanomaterial Used in Diagnosing Metabolic Disease - Zhang, Congcong; Du, Xin (Frontiers in Chemistry, 2020)
Metabolic diseases have become common diseases with the improvement of living standard because of the changed dietary habits and living habits, which seriously affect the health of people. Currently, related biomarkers have been widely used as important indicators for clinical diagnosis, treatment and prognosis of metabolic diseases. Among all detection methods for biomarkers of metabolic diseases, electrochemical sensor technology has the advantages of simplicity, real-time analysis and low cost. Carbon nanomaterials were preeminent materials for fabricating electrochemical sensors in order to enhance the performance. In this paper, we summarize the research progress in the past three years of electrochemical sensors based on carbon nanomaterials in detecting markers of metabolic diseases, which include carbon nanotubes, graphene, carbon quantum dots, fullerene and carbon nitride. Additionally, we discuss the future prospects for this field of study.